2023
DOI: 10.1007/s10571-023-01319-7
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Alteration in MPTP Mouse Model of Parkinson Disease is Administration Regimen Dependent

Abstract: Parkinson Disease (PD) is one of the most common neurodegenerative disorders characterized by loss of dopaminergic neurons involved in motor functions. Growing evidence indicates that gut microbiota communicates with the brain known as the gut-brain axis (GBA). Mitochondrial toxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is commonly used in animal studies to investigate the GBA in PD. Various MPTP administration regimens are performed in PD mouse models involving one to multiple injections in 1 day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
(155 reference statements)
0
2
0
Order By: Relevance
“…Finally, taking into account that the composition of the intestinal microbiota affects the correct functioning of this barrier [25], and that it was also shown that alterations in the composition of the intestinal microbiota can accelerate the aggregation of α-synuclein, partly through the secretion of bacterial amyloid [26], the study of the microbiota, using faecal samples from the different groups, was carried out. In this sense, it is highlighted that although it was not possible to determine whether the changes in the intestinal microbiota were a cause or a consequence of the pathogenesis of the disease, it was established that a healthy microbiota can reduce the risk of developing PD [27]. The results obtained in our model showed that richness and abundance (alpha diversity), studied with different indices, was greater in the MPTP group than in the healthy control; while the different treatments showed intermediate values.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, taking into account that the composition of the intestinal microbiota affects the correct functioning of this barrier [25], and that it was also shown that alterations in the composition of the intestinal microbiota can accelerate the aggregation of α-synuclein, partly through the secretion of bacterial amyloid [26], the study of the microbiota, using faecal samples from the different groups, was carried out. In this sense, it is highlighted that although it was not possible to determine whether the changes in the intestinal microbiota were a cause or a consequence of the pathogenesis of the disease, it was established that a healthy microbiota can reduce the risk of developing PD [27]. The results obtained in our model showed that richness and abundance (alpha diversity), studied with different indices, was greater in the MPTP group than in the healthy control; while the different treatments showed intermediate values.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic is one of these promising therapies, which have been shown to prevent gut in ammation via regulating the bacterial composition, altering the various pro-in ammatory cytokines and enhancing the gut barrier [41]. The MPTP-induced changes or dysbiosis in gut microbiota have been well studied in the rodents [42,43] and probiotics have been found to improve the gut microbiota in both diversity and richness in MPTP-treated mice [44]. VSL#3®, a probiotic cocktail containing eight cultured bacteria, is usually prescribed for treatment of irritable bowel disease via restoring the gut microbial composition.…”
Section: Discussionmentioning
confidence: 99%